Management stratigies [sic] for the reuse of wastewater in Jordan - Duqqah, Mohammad M., author; Bali, Khaled M., author; Suleiman, Ayman A., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Water resources in Jordan are extremely limited and water availability per capita is among the lowest in the world. With the expected growth in population, the already limited supply of fresh water for agriculture will be used to meet the growing demands in urban and industrial regions of the country. The sustainability of irrigated agriculture in Jordan is dependent on efficient irrigation systems such as drip irrigation and marginal water sources such as wastewater generated from wastewater treatment facilities in Jordan. The municipal and industrial water requirements in Jordan are expected to increase by 65% over the next 15 years. While agricultural demands are expected to increase by 5% during the same period. Reuse of treated municipal water is expected to increase to meet the growing urban, industrial, and agricultural demands in the future. Irrigated agriculture in Jordan is mostly concentrated in the Jordan Valley with optimum climatic conditions that allow for the production of up to three high-value vegetable crops per year. As irrigated agriculture in Jordan becomes more dependent on wastewater and other marginal water sources, the quality of marginal waters used for irrigation must be suitable for crop production. Therefore, the availability of treated wastewater for reuse to meet crop water requirements is dependent on water quality, crop type, irrigation system, and other factors. A computer model was developed to predict the potential contribution of wastewater to crop water use of major cash crops in the Jordan Valley. The model incorporates wastewater quality, irrigation system, crop type, and soil type in estimating the maximum potential contribution of wastewater to crop evapotranspiration. The model estimates the potential quantities of wastewater that can be used to supplement fresh irrigation water for each of the major crops in the Valley. The model can be used to implement sustainable management strategies for the reuse of treated wastewater in the Jordan Valley.
USCID fourth international conference
Management strategies for the reuse of wastewater in Jordan
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.